1979
DOI: 10.1289/ehp.7933227
|View full text |Cite
|
Sign up to set email alerts
|

Potential health and environmental effects of trace elements and radionuclides from increased coal utilization.

Abstract: This report addresses the effects of coal-derived trace and radioactive elements. A summary of our current understanding of health and environmental effects of trace and radioactive elements released during coal mining, cleaning, combustion, and ash disposal is presented. Physical and biological transport phenomena which are important in determining organism exposure are also discussed. Biological concentration and transformation as well as synergistic and antagonistic actions among trace contaminants are disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Van Hook, 1978Hardin et al, 1982Wagner and Greiner, 1982 All of the authors qualify their estimates in one way or another. Van Hook (1978) states that "atmospheric releases of radionuclides from increased coal combustion do not represent a significant public health problem unless coal containing greater than 5 ppm U comes into general use."…”
Section: Uranium Concentration Referencementioning
confidence: 92%
See 1 more Smart Citation
“…Van Hook, 1978Hardin et al, 1982Wagner and Greiner, 1982 All of the authors qualify their estimates in one way or another. Van Hook (1978) states that "atmospheric releases of radionuclides from increased coal combustion do not represent a significant public health problem unless coal containing greater than 5 ppm U comes into general use."…”
Section: Uranium Concentration Referencementioning
confidence: 92%
“…Van Hook (1978) states that "atmospheric releases of radionuclides from increased coal combustion do not represent a significant public health problem unless coal containing greater than 5 ppm U comes into general use." It is not clear whether "general use" implies one plant burning such coal over an extended period of time or most plants burning such coal over an extended period.…”
Section: Uranium Concentration Referencementioning
confidence: 99%
“…Many of these elements are thought to be toxic to animal and plant life (Van Hook, 1978). Gluskoter et al (1977) found that Illinois Basin coals have relatively high content of boron, beryllium, bromine, cadmium, germanium, manganese, nickel, lead, zinc, iron, and sulfur.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Slag is that portion of total ash which melts to a viscous fluid at combustion temperatures, and bottom ash is the remainder that does not melt and is too heavy to be entrained in flue gas. 8 Depending on coal composition and furnace design, ashes can be carried in the flue gas (fly-ash) or deposited underneath the boiler (bottom ash). In coal-fired power plants, the characteristics of fly-ash and bottom ash are similar; they are mixtures of inorganic mineral constituents of the burned fuel and organic material that is not completely combusted.…”
Section: Coal Combustionmentioning
confidence: 99%